An efficient one-pot synthesis of 2-bromo-6-aryl[5H]pyrrolo[2, 3-b]pyrazines. Issue 12 (18th March 2015) - Simpson, Iain; St-Gallay, Steve A.; Stokes, Stephen; Whittaker, David T.E.; Wiewiora, Rafal
Graphical abstract: Abstract: We report a two step one-pot method for the synthesis of 2-bromo-6-aryl[5 H ]pyrrolo[2, 3- b ]pyrazines. The process makes use of a cleaner copper-free Sonogashira coupling and an improved base-mediated 5- exo -dig cyclisation to afford the products in good yields. This method expands the scope to structures that are poorly represented in the literature and incorporates a halide for further synthetic elaboration.